The Role of Serine-Threonine Kinase Receptor-Associated Protein (STRAP) Signaling in Cancer - Sourajeet Karfa; Shashank Saurav; Bryan Feng; Song Li; Brian K. Law; Pran K. Datta (Cells, 2025)
STRAP (serine-threonine kinase receptor-associated protein), a WD domain-containing 38.5 kDa protein, was first identified in TGF-ß signaling and participates in scaffold formation in numerous cellular multiprotein complexes. It is involved in the regulation of several oncogenic biological processes, including cell proliferation, apoptosis, migration/invasion, tumor initiation and progression, and metastasis. STRAP upregulation in epithelial tumors regulates several signaling pathways, such as TGF-ß, MEK/ERK, Wnt/β-Catenin, Notch, PI3K, NF-κB, and ASK-1 in human cancers, including colon, breast, lung, osteosarcoma, and neuroblastoma. The upregulation of STRAP expression is correlated with worse survival in colorectal cancer following post-adjuvant therapy. Strap knockout sensitizes colon tumors to chemotherapy, delays APC-induced tumor progression, and reduces cancer cell stemness. The loss of Strap disrupts lineage differentiation, delays neural tube closure, and alters exon skipping, resulting in early embryonic lethality in mice. Collectively, the purpose of this review is to update and describe the diversity of targets functionally interacting with STRAP and to rationalize the involvement of STRAP in a variety of signaling pathways and biological processes. Therefore, these in vitro and in vivo studies provide a proof of concept that lowering STRAP expression in solid tumors decreases tumorigenicity and metastasis, and targeting STRAP provides strong translational potential to develop pre-therapeutic leads.